The Influence of Sufism on Social Practices in Contemporary Muslim Societies: A Case Study in Indonesia - St. Rahmah; Akhmad Hasan Saleh; Sri Nur Rahmi (Journal of Noesantara Islamic Studies, 2024)
Sufism, emphasizing spirituality and inner transformation, has significantly shaped the cultural and social practices of Muslim communities, including in Indonesia. Despite its widespread influence, the specific ways Sufism impacts modern social practices are underexplored, particularly in regions where Sufi traditions have adapted to societal changes. This study examines the influence of Sufism on social practices in contemporary Muslim societies, focusing on Indonesia. It explores how Sufi teachings shape social behaviors, community structures, and intergroup relations, and investigates the role of Sufi orders (tariqas) in promoting social cohesion and addressing modern issues. Using a qualitative case study approach, the research employs ethnographic methods like participant observation and in-depth interviews in regions with strong Sufi traditions, such as Java and Sumatra. Thematic analysis reveals that Sufism promotes values like tolerance, communal harmony, and social justice. Sufi rituals and gatherings foster community building and interfaith dialogue, enhancing unity and mutual respect. The study also finds that Sufi teachings have adapted to address contemporary challenges like radicalism and social fragmentation, reinforcing their relevance in modern Indonesian society. The study concludes that Sufism plays a vital role in shaping Indonesia’s social fabric, contributing to social cohesion and offering a counter-narrative to more rigid Islamic interpretations.